Experiences and perceptions of employees and healthcare professionals on a multidisciplinary program for the secondary prevention of low back pain - Lisa Bernaers; Tine Marieke Willems; Gia Hien Lam; Morgane Mahy; Dorina Rusu; Christophe Demoulin; Dominique Van de Velde; Lutgart Braeckman (Scientific Reports)
Abstract Low back pain (LBP) can lead to disability and sick leave, impacting work participation and overall health. Given the complex and multifactorial nature of LBP, Belgium’s Federal Agency for Occupational Risks (FEDRIS) promotes a secondary prevention strategy for LBP among workers engaged in ergonomically demanding tasks. This strategy includes multidisciplinary-based rehabilitation (MBR) and an optional workplace intervention. This paper explored the experiences and perceptions of employees and healthcare professionals (HCPs) regarding the secondary prevention program with a focus on the MBR component, aiming to identify its strengths, challenges, and potential solutions. A multicenter qualitative design involving six semistructured focus groups was employed. The participants included 15 employees who attended the program because of LBP and 24 HCPs involved in its delivery. The data were analyzed via thematic analysis. Three major themes were identified: functional and work-related outcomes, content-related factors, and duration and continuation. Positive outcomes included improvements in pain, function, and return to work (RTW), with workplace adaptations and ergonomic guidance playing key roles. Success factors such as education, exercise therapy, motivation, and social interaction were highlighted. However, challenges were identified, including limited communication between centers and employers, insufficient psychological support, and a lack of follow-up to sustain the program’s effects. This qualitative evaluation highlights that person-centered, biopsychosocial approaches—encompassing individualized education, ergonomic adaptations, and psychological support—are crucial for optimizing the FEDRIS MBR program’s long-term impact on LBP and RTW outcomes. Consistency in staffing, structured follow-up, and systematic prescreening are key areas for improvement. Although limited by a small sample size and retrospective design, these findings pinpoint actionable refinements that future longitudinal studies can explore to ensure sustained, cost-effective rehabilitation benefits.